Ethnomedicine of Santal tribe living around Susunia hill of Bankura district, West Bengal, India: The quantitative approach - Chowdhury Habibur Rahaman,Suman Karmakar (Journal of Applied Pharmaceutical Science, 2015)
The present paper deals with the observations on ethnomedicinal uses of wild plants by the Santal tribal people of villages surrounding the Susunia hill of Bankura district, West Bengal. Data were collected by interviewing Santal medicine men and knowledgeable persons with the help of semi-structured and open-ended questionnaire. The data have been analyzed employing suitable statistical tools like Informant Consensus value for Plant Part (CPP), Consensus Factor (Fic), Fidelity Level (FL%), Preference ranking exercise, Importance value (IVs) and Pearson Correlation Coefficient (PCC). Altogether 25 plants have been recorded which are used by the Santal people in formulation of 40 ethnomedicinal preparations for curing 27 types of diseases. Leaves secured the highest CPP value (0.33). Circulatory system disorder, Nervous System disorder and Birth/Puerperium disorder secured the highest Fic value (1). Abrus precatorius L., Ampelocissus latifolia (Roxb.) Planch., etc. secured the highest FL value(100%). Curcuma longa L. has been identified as most preferred species by preference ranking exercise. The highest score of IVs observed in Borassus flabellifer L., Cajanus cajan (L.) Millsp.,etc. The PCC between IVs and FL was 0.679 showing moderate positive significant association. Bioassay of these ethnomedicinal remedies has to be carried out further for their scientific validation.
Keywords: Susunia hill,ethnomedicine,Informant consensus,factor,Fidelity level,Preference ranking exercise.